(3GdcfhR aj ac GdQehRs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg Ydi LRjd fYeGFg GdGVGaI hgh Cf jchf GdPcQ hRf GdCfKi HYO GdJaUjd Cj EPG aUdJ hCQOJ GdLeY adjcf GdhRf ShGA HShGA hGdeQGO gG gfG GdhRf Gdcej s
(3BNQgG (B:s
(3hEPG ONdJ Ydi GdSJI CbSGe ef GdeGA GdHGbjI GdeYOI ddMeQI hXgQJ Ydi GdeQcJ GdMeQI GdaQajQjI agh MjfFP GcSjQ GdMeQI hgh OhQ GdTeS hOhQ GdMjGI GdCHOjI hGdchf hGdfTCI GdBNQI hbO Je hceds
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs